1966
DOI: 10.1073/pnas.56.6.1844
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-Specific Proteins in E. Coli Infected With an Rna Bacteriophage

Abstract: The f2 group of RNA coliphages (f2, MS2, R17, fr), first isolated by Loeb and Zinder,1 are closely related, small viruses with single-stranded RNA of about one million molecular weight (for a review of RNA phages, see ref.2). The number of proteins encoded in the viral RNA is therefore small. To date, two phage-specified proteins have been identified chemically or enzymatically in infected cells, the phage coat subunit and an RNA synthetase,3-5 and the presence of a third protein has been inferred from genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Expression of maturation/lysis protein in RNA coliphage Qb is tightly regulated, and is primarily required late in the infectious cycle for both capsid formation and host cell lysis (Nathans et al, 1966;Karnik & Billeter, 1983;Winter & Gold, 1983; for a review, see van Duin, 1988). Translational downregulation of the Qb maturation gene (nucleotides 61 through 1320) has been shown to involve an extremely stable, long-range RNA loop structure comprising nearly 470 nucleotides at the 5 H end of the genome (de Smit & van Duin, 1990, 1994.…”
Section: Introductionmentioning
confidence: 98%
“…Expression of maturation/lysis protein in RNA coliphage Qb is tightly regulated, and is primarily required late in the infectious cycle for both capsid formation and host cell lysis (Nathans et al, 1966;Karnik & Billeter, 1983;Winter & Gold, 1983; for a review, see van Duin, 1988). Translational downregulation of the Qb maturation gene (nucleotides 61 through 1320) has been shown to involve an extremely stable, long-range RNA loop structure comprising nearly 470 nucleotides at the 5 H end of the genome (de Smit & van Duin, 1990, 1994.…”
Section: Introductionmentioning
confidence: 98%
“…and electrophoretic behavior of the f2 and MS2 proteins has received much attention (19,25,26). Of the three known viral proteins, the largest has been identified as the product of the replicase cistron and is known to be hyperproduced by coat mutants of MS2 and f2 (25,27).…”
Section: Resultsmentioning
confidence: 99%
“…cells, but not in uninfected cells after actinomycin (25) or rifampicin treatment (P. Model, N. Fedoroff, unpublished observations). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed mechanism of the translation of MS2 RNA has been well investigated both in vivo [11] and in vitro [12] . Nathans [13] has shown that the ®ngerprint of the product in E. coli cell-free system shows the same pattern of that of the coat protein expressed in E. coli cell in which the coat protein can be measured as a major spot.…”
Section: Cell-free Translation Of Bacteriophage Ms2 Rna In a Microreamentioning
confidence: 99%